(untitled) (Circe de clásicos y modernos, 2018)
The brief text of the Didaché was ‘rediscovered’ a hundred and thirty-six years ago (1873) and it was edited for scholarly reading and analysis in 1883. Since then, several theories and interpretations have been proposed so as to its authors’ identity, the audi-ence it was written for, the sources and theological perspectives as well as the ecclesiology underlying the intricate tapestry of the topics which are considered to be foundations of the Western Christianity. Our aim in this paper is to look into the net of later rewritings for the Jew features, which can be clearly perceived as an early stratum in chapters 1-6 –referring to the moral teaching of the two ways–, in chapter 7 –related to the baptism– and in chapters 9-10 and 14 related to the Eucharistic.